Measuring direct non-medical burden among patients with advanced non-small cell lung cancer in China: is there a difference in health status? - Xia, Yu; Chen, Yingyao; Chen, Jia; Gan, Yuying; Su, Chunxia; Zhang, Haibo; Long, Enwu; Yan, Fei; Yang, Yi (Frontiers in Public Health, 2023)
Objective This study was conducted to estimate direct nonmedical cost of advanced non-small cell lung cancer (NSCLC) patients and explore whether its associated factors vary by health status. Methods Data were obtained from 13 centers in 5 provinces for patients with advanced NSCLC in China. The direct nonmedical cost of patients since the patients were diagnosed with NSCLC included cost of transportation, accommodations, meal, hired caregiving and nutrition. We measured patients’ health status by EQ-5D-5L instrument, and divided them into good (≥0.75) and poor (<0.75) groups based on the utility score. Generalized linear model (GLM) was used to assess independent associations between statistically significant factors and nonmedical financial burden in health status subgroups. Results Data from 607 patients were analyzed. The direct nonmedical cost associated with advanced NSCLC since diagnosis was 2951 per case (4060 in poor health group, and 2505 in the other), with nutrition cost the most. GLM results showed that insurance plan (Free medical service vs. No insurance: 19986.5, [2957.1, 37015.9]), hospitalization frequency (359.0, [213.3, 504.8]), and average length of hospital stay (296.1, [73.5, 518.7]), were independent factors influencing direct nonmedical cost in the poor health group. Among participants with good health status, caregiving time per day (6 9 hours per day vs. less than 3 hours per day: 2518.3, [422.9, 4613.8]; more than 9 hours per day vs. less than 3 hours per day: 2323.9, [975.6, 3672.3]), duration of disease (82.0, [52, 112]), and hospitalization frequency (211.5, [144.9, 278.1]) were statistically associated factors. Conclusion The direct nonmedical burden of advanced NSCLC patients in China is considerable and differs by health status. Strengthening accessibility for more effective therapies and early nutritional intervention to improve prognosis, and further promoting accessible care forms within relevant healthcare insurance coverage may be potentially feasible approaches to alleviate direct nonmedical economic burden for patients and their families.